Dyskurs o rodzinie na łamach „Przeglądu Powszechnego” w II Rzeczypospolitej - Topij-Stempińska, Beata (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2015)
„Przegląd Powszechny” was founded in 1884 by a Polish Jesuit Marian Morawski. This monthly periodical aimed at promoting the knowledge of Catholic principlesamong intellectuals and to reflect upon the current issues concerning social, academic, or literary life. Extensive articles in the fields of literature, history, philosophy, theology, religious studies, social ethics were published. Regular columns referred to the contemporary national, social, cultural and religious issues as well as book reviews. One of the social issues raised in the periodical was the problems concerning the contemporary family. The authors drew attention to the role of the family in educating; they addressed issues concerning pro-family education. They provided interpretation for the “legal aspect of the issue” regarding divorce or abortion. Through their contributions, they also wanted to sensitize the readers to the situation of Polish children in the family, or the necessity of health education for the Polish family.
Keywords: family; marriage; pro-family education; health education; periodical; The Second Republic of Poland